NILAI BUDAYA DALAM TEKS SINRILIK KAPPALAK TALLUMBATUA SERTA RELEVANSINYA TERHADAP PENDIDIKAN KARAKTER DI SMA - Asri, Aswati; Daeng, Kembong; Asia (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
This study aims to: (1) find and describe the embodiment of cultural values ​​in the Kappalak Tallumbatua Sinrilik text, and (2) the relevance of cultural values ​​in the Kappalak Tallumbatua Sinrilik text to the character education of high school students. This research uses descriptive qualitative method. The object of research is the various cultural values ​​contained in the Sinrilik Kappalak Tallumbatua text and their relevance to character education for high school students. The data in this study are in the form of paragraphs, sentences, and words related to cultural values ​​in the Kappalak Tallumbatua Sinrilik Text and the 1993 translation of Aburaerah Arief and Zainuddin Hakim and the curriculum for high school level Makassar Language subjects. Collecting research data through reading - listening techniques and note taking techniques. The data analysis technique is through reading, identification, classification, analysis, and drawing conclusions. The results showed: (1) Cultural values ​​include; (a) cultural values ​​in human relations with God which consist of piety, piety, belief in destiny, gratitude, and desire, (b) cultural values ​​in human relations with society which consist of values ​​of deliberation, mutual cooperation, harmony or balance . and solidarity, (c) cultural values ​​in human relations with each other, which consist of the values ​​of love, loyalty, obedience to parents, and wisdom, (d) cultural values ​​in human relations with oneself which consist of the values ​​of willingness, learning, respect high in customs and religion, courage and vigilance, and (e) cultural values ​​in the relationship between humans and nature, consisting of human values ​​that are integrated with nature and humans who control or exploit nature. (2) The text of the Sinrilik Kappalak Tallumbatua is very relevant to character education for high school students, including religious character, honesty, hard work, love of peace, responsibility, love for the country